2017
DOI: 10.1038/s41598-017-04573-0
|View full text |Cite
|
Sign up to set email alerts
|

The Arctic-Subarctic sea ice system is entering a seasonal regime: Implications for future Arctic amplification

Abstract: The loss of Arctic sea ice is a conspicuous example of climate change. Climate models project ice-free conditions during summer this century under realistic emission scenarios, reflecting the increase in seasonality in ice cover. To quantify the increased seasonality in the Arctic-Subarctic sea ice system, we define a non-dimensional seasonality number for sea ice extent, area, and volume from satellite data and realistic coupled climate models. We show that the Arctic-Subarctic, i.e. the northern hemisphere, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…These results expand on an analysis by Kinnard et al (2008) who found a gradual expansion of the SIZ since 1870 with a marked acceleration over the satellite era. The seasonality of Arctic sea ice has also been quantified by Haine and Martin (2017) using a metric to describe the annual range in SIE (winter max-summer min). They show that the seasonality of Arctic sea ice is increasing, driven largely by the record low summer SIE observed in recent years, which is also evident in our SIZ extent for Arctic Ocean regions ( figure 3).…”
Section: Siz Extentmentioning
confidence: 99%
“…These results expand on an analysis by Kinnard et al (2008) who found a gradual expansion of the SIZ since 1870 with a marked acceleration over the satellite era. The seasonality of Arctic sea ice has also been quantified by Haine and Martin (2017) using a metric to describe the annual range in SIE (winter max-summer min). They show that the seasonality of Arctic sea ice is increasing, driven largely by the record low summer SIE observed in recent years, which is also evident in our SIZ extent for Arctic Ocean regions ( figure 3).…”
Section: Siz Extentmentioning
confidence: 99%
“…Several positive feedbacks may be responsible for the rapid pace of shrinking sea ice extent. Sea ice loss is marked by an 1540 increasing transition from multi-year to seasonal sea ice, which is thinner and therefore more vulnerable to melt (Haine and Martin, 2017). First-year sea ice has increased from 40% to 60-70% of Arctic sea ice area between 1984 And 2018 .…”
Section: Rapid Decline Of Arctic Sea Ice Extent Risks Episodic Ice-frmentioning
confidence: 99%
“…For these reasons the Arctic is particularly vulnerable to climate change. In the coming decades we may expect to enter a new regime, in which the interior Arctic Ocean is entirely ice free in summer and sea ice is thinner and more mobile in winter (e.g., Haine & Martin, ). Some climate model scenarios suggest that the Arctic Ocean may be seasonally ice free by ∼2050 (Collins et al, ).…”
Section: Introductionmentioning
confidence: 99%